Bank holding companies and government support issues - Royce, Colleen (Banks and banking developments series., 2015)
During the 2007-09 financial crisis, the federal government's actions to stabilize the financial system provided funding support and other benefits to bank holding companies and their subsidiaries. Agencies introduced new programs with broad-based eligibility that provided funding support to eligible institutions, which included entities that were part of a bank holding company and others. Programs that provided the most significant support directly to bank holding companies or their subsidiaries included Department of the Treasury capital investment programs, Federal Reserve System lending pr.